ADVERSE EVENTS DURING TREATMENT OF PATIENTS SUFFERING FROM MULTIPLE DRUG RESISTANT TUBERCULOSIS - D. Yu. Schegertsov; O. V. Filinyuk; L. N. Buynova; N. A. Zemlyanaya; N. N. Kabanets; A. S. Alliluev (Туберкулез и болезни лёгких)
Objective: to perform retrospective analysis of the ranges, structure, degree of severity and time of development of adverse events in tuberculosis patients with multiple drug resistance on treatment and to assess their impact on chemotherapy duration Results. Totally, 1387 adverse events were registered Out of 500 patients, adverse events occurred in 437 (874%) Intestinal (293 patients, 670%) and metabolic (297 patients, 680%) adverse events prevailed Each second patient developed neurological and hepatotoxic adverse events (222 (508%) and 175 (400%) respectively) Dermatological adverse events, ototoxicity, hypothyrosis, and nephrotoxicity were observed in 123 (281%), 114 (261%), 72 (165%), and 56 (128%) patients respectively 21 (48%) patients had adverse events affecting vision 14 (32%) patients suffered from peripheral neuropathy On average, one patient had adverse events affecting three systems of the host If one patient had three different types of adverse events and more, the duration of treatment made more than 700 days Each fourth MDR TB patient (2494%) had severe adverse eventsConclusions. Adverse events occurring during treatment of multiple drug resistant tuberculosis are manifested through arthralgia, intestinal and central nervous system disorders In order to prevent adverse events laboratory abnormalities and clinical manifestations are to be monitored on a regular basis